2013
DOI: 10.1155/2013/810547
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Parameters by Using Response Surface Methodology, Purification, and Identification of Anthocyanin Pigments in Melastoma malabathricum Fruit

Abstract: Anthocyanins not just have various benefits in food industry but also have been used as natural colourants in cosmetic, coating products and as potential natural photosensitizers in solar cell. Thus, the main purpose of this study was to obtain information on the maximum yield of anthocyanin that can be recovered from Melastoma malabathricum fruit. Factors such as extraction temperature, extraction time, and solid to liquid ratio were identified to be significantly affecting anthocyanin extraction efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 16 publications
1
39
0
2
Order By: Relevance
“…A similar observation was found in the study of Hu et al () who reported that saponin yield of Eclipta prostrasta L. leaves increased gradually when the ultrasonic temperature increased from 40 to 70 °C. Heating provides energy and encourages molecules in the system to vibrate strongly, thus, breaking the bonds among compounds and cell membranes and liberating compounds into the solvent (Anuar, Adnan, Saat, Aziz, & Taha, ). However, higher temperature enhanced the oxidation reaction and thermal degradation of saponins, leading to a fall in saponin yield.…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was found in the study of Hu et al () who reported that saponin yield of Eclipta prostrasta L. leaves increased gradually when the ultrasonic temperature increased from 40 to 70 °C. Heating provides energy and encourages molecules in the system to vibrate strongly, thus, breaking the bonds among compounds and cell membranes and liberating compounds into the solvent (Anuar, Adnan, Saat, Aziz, & Taha, ). However, higher temperature enhanced the oxidation reaction and thermal degradation of saponins, leading to a fall in saponin yield.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to Figure , the residuals were studentized and the values were greater than +2 and less than −2. It shows that the residuals followed a normal distribution and the majority of the data points are distributed along the fitted line, which are fairly close with reasonable outliers (Anuar, Mohd Adnan, Saat, Aziz, & Mat Taha, ).…”
Section: Resultsmentioning
confidence: 58%
“…In this work, the barrel temperature, feed moisture content and feed soybean composition were all set within range (100 to 140 o C; 15 to 25%; 8 to 24%) as defined by the preliminary study (Table 1), while the goal for the response variables of bulk density, expansion index and lightness chroma levels were set at maximum, and a* and b* set at minimum (Table 6). Anuar et al (2013) reported that when goal was set at 5, the response target objective was to meet the objective of getting response at a maximum level. Results of the numerical optimization therefore indicated that the optimum extrusion variables were 130 o C (barrel temperature), 20% (feed moisture level) and 23% (feed soybean composition) (Table 6), while optimum responses in terms of bulk density, expansion index, lightness, redness and yellowness indices were 0.21g cm −3 , 128.9%, 17.1, 3.13 and 24.5, respectively.…”
Section: Optimization Process Variablesmentioning
confidence: 99%